A systematic review of the associations between age and sex and the operative risks of carotid endarterectomy. - Bond, R; Rerkasem, K; Cuffe, R; Rothwell, P (2005)
BACKGROUND: Randomized trials of carotid endarterectomy (CEA) for both symptomatic and asymptomatic carotid stenosis have demonstrated that benefit is decreased in women, due partly to a high operative risk, which is independent of age. However, it is uncertain whether these trial-based observations are generalisable to routine clinical practice. METHODS: We performed a systematic review of all publications reporting data on the association between age and/or sex and procedural risk of stroke and/or death following CEA from 1980 to 2004. RESULTS: 62 eligible papers reported relevant data. Females had a higher rate of operative stroke and death (25 studies, OR = 1.31, 95% CI = 1.17-1.47, p < 0.001) than males, but no increase in operative mortality (15 studies, OR = 1.05, 95% CI = 0.81-0.86, p = 0.78). Compared with younger patients, operative mortality was increased at > or =75 years (20 studies, OR = 1.36, 95% CI = 1.07-1.68, p = 0.02), at age > or =80 years (15 studies, OR = 1.80, 95% CI = 1.26-2.45, p < 0.001) and in older patients overall (35 studies, OR = 1.50, 95% CI = 1.26-1.78, p < 0.001). In contrast, risk of non-fatal stroke did not increase with age and so the combined perioperative risk was only slightly increased at age > or =75 years (21 studies, OR = 1.18, 95% CI = 0.94-1.44, p = 0.06), at age > or =80 years (10 studies, OR = 1.14, 95% CI = 0.92-1.36, p = 0.34) and in older patients overall (36 studies, OR = 1.17, 95% CI = 1.04-1.31, p = 0.01). CONCLUSIONS: The effects of age and sex on the operative risk of CEA in published case series are consistent with those observed in the trials. Operative risk of stroke is increased in women and operative mortality is increased in patients aged > or =75 years.